Effect of adding palm frond waste and spraying with tryptophan on the vegetative growth traits of olive seedlings of Manzanillo and Bashiqi cultivars - Thanun Abdul Hussein Hade; Susan Mohammed Al-Rubaei (Journal of Kerbala for Agricultural Sciences, 2024)
The experiment was carried out in the plant canopy of the Department of Horticulture and Landscape Engineering/College of Agriculture, University of Kerbala, located in the Al-Husseiniyah area in Kerbala Governorate, on 11/10/2023. The experiment aimed to determine the best level of palm frond waste, along with determining the best concentration of tryptophan acid and the extent of their effect. On some characteristics of vegetative growth of olive seedlings, the experiment was carried out according to a randomized complete block design (RCBD) according to the order of the factorial experiment, with three replications. The first factor included two varieties of olive (Manzanillo and Bashiqi), while the second factor included three levels of palm frond waste (0, 3% and 6%) and the third factor included three concentrations of tryptophan acid (0, 75 and 150 ml L-1). The results showed that the Manzanillo cultivar excelled in seedling height, stem diameter, number of leaves per seedling, leaf area, relative moisture content of leaves, and the percentage of dry matter of the shoot system, with averages of (25.385 cm, 2.083 mm, 537.60 leaf seedling-1, 21.497 cm2, 77.615% and 61.071% respectively). It was also noted that the addition of palm frond waste had a significant effect, as the third level (6%) excelled in all of the aforementioned traits with averages of (28.811 cm, 2.442 mm, 611.50 leaf seedling-1, 24.648 cm2, 79.977%, and 70.957%). As for spraying with tryptophan acid, it was observed that the concentration (150 ml L-1) was superior to the same traits with averages of (24.689 cm, 2.124 mm, 529.50 leaf seedling-1, 21.351cm2, 76.760% and 61.894%). The results also showed that the interactions between the factors were significant in all the characteristics under study.